Evolution and Trend Analysis of Research Hotspots in the Field of Pollution-Intensive Industry Transfer—Based on Literature Quantitative Empirical Study of China as World Factory - Feng, Langang; Shang, Shu; Feng, Xin; Kong, Ying; Bai, Jiahe (Frontiers in Environmental Science, 2022)
[Background] The transfer of pollution-intensive industries in China accounts for an increasing proportion of industrial transfer, and related studies emerge endlessly. Fully exploring its research and development's breadth and depth will help clarify the development trend in this field and provide a quantitative basis for policy formulation. [Method/Process] From the perspective of bibliometric analysis, with keywords as the core and cluster analysis of research hotspots as the basis, the keywords of pollution-intensive industry transfer in CNKI database are analyzed by CiteSpace software and divided into five categories. Established the text corpus model, and the network analysis transformed into a visual form. Due to the diverse research hotspots in pollution-intensive industry transfer, this paper analyzes the evolution of research hotspots in this field to predict its future development trend.[Conclusion/Significance] China, as the world's factory, is affected by relevant policies, and industrial transfers have generally occurred. Industrial transfer, especially the transfer of pollution-intensive industries, has gradually attracted the attention of academic circles and has become a hot topic. When dealing with the transfer of pollution-intensive industries, industrial transfer only transfers pollution across regions. If we want to reduce pollution from the source, innovation is an essential means. There were few articles about the emerging polluting industries in the past, but now it is the emerging polluting industries that mainly produce pollution, so it deserves academic attention. The mainstream measurement methods, the related share index method and the input-output table have their shortcomings. The deviation share method can overcome the shortcomings of both, which can be used as a reference for scholars to measure the transfer of pollution-intensive industries in the future.